Sejarah Santri dalam Revolusi 1945: Analisis Peran dalam Melawan Penjajah - Wasid, Wasid; Amiq (Qurthuba: The Journal of History and Islamic Civilization, 2026)
This research raises the topis of “The History of Santri in the 1945 Revolution: Analysis of the role in Fighting the Colonizers”. There are twon formulations of the problem that will be answered: (1) What were the origins of the 1945 revolutionary war? (2) What is the form and role of the upheaval of the Santri against the colonizers, especially in 1945? To answer these three problems, the researcher uses a historical approach with heuristic methodological flows, verification, interpretation, and hysterography. In addition, the author also uses role theory to analyze the processes carried out by students during the 1945 revolution. From the findings and discussion of the research, it can be concluded that: (1) the origins of the 1945 revolutionary war began with the arrival of the NICA, which rode on the backs of the allies, in Indonesia. The NICA wanted to regain control of Indonesia, with the Dutch as its driving force, leading to resistance from the people, including Santri. (2) The were two strategic roles for the Santri in the 1945 revolutionary war: strengthening their fighting spirit by declaring this war a jihad, and strengthening theis ranks by joining militias such as the Hizbullah and Sabilillah.